Indenter misalignment in impression creep test: Uncertainty, correction and recommendation. (February 2022) - Li, Suo; Deng, Dean; Sun, Wei
The impression creep test (ICT) method, as a miniature specimen test technique, has been used extensively to determine the in-service creep properties of power plant components. However, the experiment results of the ICT can be affected by some uncertainties associated with the inaccuracies of measurement, which have not been studied before. This paper presents some results of finite element analyses, to evaluate the effect of indenter misalignment on the results of the ICT, such as the steady-state creep deformation rate and the conversion parameters. The results obtained have shown that the angular misalignments of the indenter around horizontal directions have a relatively significant influence on the conversion parameters, and the misalignment around vertical direction has a much less significant effect. Empirical formulas were developed for the possible correction of the conversion factors. Finally, some recommendations on the control of the indenter and specimen alignment were given.